The Impact of Water Pollutants on the Hydrological Characteristics of the Euphrates River in the City of Nasiriyah (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
Water Pollution: Water pollution constitutes one of the significant challenges facing urban areas in most countries across the globe. Technological changes and industrialization have resulted in the use of significant amounts of water to support and maintain industrial processes, aside from the amounts used for domestic and agricultural purposes. Consequently, the amounts and types of waste and residue arising from such use have ended up affecting natural sources of water, namely surface and groundwater, upon disposal into such sources without prior treatments. This has resulted in modifications to the quantities and quality attributes associated with water, with consequent environmental influences adversely affecting the use of water for various purposes. The study established the existence of various factors influential in shaping the hydrological property attributes associated with water, symbolized by the geological structure and surfaces, as well as the modification attributed to the influences of environmental elements for potentially increasing the challenge associated with water pollution in the Euphrates River. The study also established the forms and sources associated with such pollutions, alongside the modifications to the various levels and forms associated with the use of water arising from modifications to its hydrological property attributes. The study also explained various important approaches associated with curtailing such levels and forms associated with water pollution and its harmful environmental influences.